PEMIDANAAN TERHADAP PELAKU TINDAK PIDANA YANG DISEBABKAN PENGARUH MINUMAN KERAS DI KABUPATEN SOLOK SELATAN DI TINJAU SECARA SOSIOLOGI - Emi Handrina (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2020)
The problem of liquor can not be denied in the life of society. Liquor is believed to not only endanger the wearer, but can also bring a very bad impact in the environment even though consuming liquor is the right of every individual as long as it does not interfere with the order. Deviations that occur especially the habit of consuming excessive liquor to cause loss of self-consciousness or can be said to be drunk which ultimately lead to violations and even criminal acts are very disturbing society. In examining and adjudicating a case, the judge is bound by the procedural law, which governs since the examination and disconnection. And the results of that examination that will be the material consideration to take the verdict. The facts revealed in the trial are the main ingredients for consideration in a verdict, so the accuracy, foresight and intelligence in presenting / finding facts of a case is an important and decisive factor to the outcome of the verdict. It is not surprising that what is in the public mind can be different from the judge's decision. In giving a judge's decision should be able to give consideration of incriminating or lightening for the perpetrators of criminal acts caused by the influence of liquor. General provisions of article 1 point 11 of the Criminal Procedure Code stipulates that a court decision is a declaration of a judge pronounced in an open court, which may be a crime or freedom or freedom from all lawsuits in all matters and in the manner prescribed by law.